The Federalist Papers - Hamilton, A. author. aut Link
XIV, 298 p. 4 illus.
Keywords: Thisbook is distinctive because it will be a political science oriented introduction to The Federalist Papers. As most of the editions have introductions by historians, and some of them quite good, there is no readily available edition with a political science focus. Such a focus would not ignore the historical dimensions of the founding and that particular era, but would supplement this historical background with a concentration on the key questions political scientists tend to ask when reading and teaching The Federalist Papers. Questions of power, separation, blending, federalism, and structural design and how they impact the practice of government, questions we political scientists ask, will be the central feature of this edition. The primary audience for this edition would be courses in American Political Thought, American Government (most of which include components of the Federalist Papers) plus courses on the Presidency, Congress, The Judiciary, and Federalism.